28.7k views
4 votes
2) Solve the Equation

2) Solve the Equation-example-1
User GPP
by
5.0k points

2 Answers

3 votes
a= 0

since you are simplifying both sides
-3= a-6/2 turns into -3 = 1/2a+-3 by distribution. then you flip the equation 1/3a-3=-3 and add 3 to both sides 1/2a-3+3=-3+3. resulting in 1/2a=0. multiple both sides by 2 giving you a=0
User Noam Nevo
by
4.9k points
4 votes

Answer:

0

Explanation:

User Adolphus
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.